Dynamic perfusion CT in brain tumors. Issue 12 (December 2015) - Yeung, Timothy Pok Chi; Bauman, Glenn; Yartsev, Slav; Fainardi, Enrico; Macdonald, David; Lee, Ting-Yim
Highlights: Basic principles of PCT. Correlation with histopathologic markers and tumor grade. Differentiation of high-grade gliomas from other brain lesions. Differentiation of true progression from post-treatment effects. Prediction of prognosis. Strengths and challenges of PCT. Abstract: Dynamic perfusion CT (PCT) is an imaging technique for assessing the vascular supply and hemodynamics of brain tumors by measuring blood flow, blood volume, and permeability-surface area product. These PCT parameters provide information complementary to histopathologic assessments and have been used for grading brain tumors, distinguishing high-grade gliomas from other brain lesions, differentiating true progression from post-treatment effects, and predicting prognosis after treatments. In this review, the basic principles of PCT are described, and applications of PCT of brain tumors are discussed. The advantages and current challenges, along with possible solutions, of PCT are presented.